Kejadian Drug-Related Problems (DRPs) Pada Pasien HIV dengan koinfeksi Tuberkulosis di Rumah Sakit Rujukan Jawa Tengah, Indonesia - Maulida Arifiani; Zakky Cholisoh (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Introduction: Tuberculosis and human immunodeficiency virus (TB-HIV) co-infection necessitates complex combination therapy using antituberculosis drugs (ATD) and antiretroviral therapy (ARV), significantly increasing the risk of drug-related problems (DRPs). However, data on DRPs patterns among TB-HIV patients in Indonesian referral hospitals remain limited. Objective: This study aimed to identify and describe the types and prevalence of DRPs among TB-HIV outpatients at a referral hospital in Central Java, Indonesia. Methods: A descriptive observational study with a retrospective approach was conducted using medical records of TB-HIV outpatients from January 2024 to December 2025. A total of 111 patients meeting the inclusion criteria were selected using total sampling. DRPs were identified based on Cipolle's classification, covering indication, effectiveness, safety, and adherence-related problems. Results: Most patients were male (66.7%), adults (71.2%), received the HRZE regimen (91.0%), received TDF+3TC+EFV antiretroviral therapy (53.2%), and were in the intensive phase of tuberculosis treatment (91.0%). The majority experienced ≥3 DRPs (64.9%), with a mean of 2.98 DRPs per patient. The most prevalent DRPs were drug interactions reducing drug concentration or therapeutic effects (97.3%), followed by drug interactions increasing drug concentration or toxicity (62.2%), need for additional drug therapy (37.8%), and medication non-adherence (34.2%). Conclusion: DRPs were highly prevalent among TB-HIV patients, predominantly involving drug interactions that may reduce treatment effectiveness or increase toxicity. Routine therapeutic monitoring and clinical pharmacist-led medication reviews are essential to optimize treatment outcomes in TB-HIV patients.